(588) Choice Of Techniques For The Public Sector In The U.A.R اختيار التقنيات للقطاع العام في جمهورية مصر العربية - A. Mongy, Mohamed; M. Elewa, Aida (INP, 2024)
The research addresses the choice of techniques in the public sector in the United Arab Republic (Egypt), beginning with an introduction to the problem of selecting appropriate techniques. It discusses the role of the public sector in this choice and its impact on industrial development. The importance of industrial estates in providing a conducive environment for effective technique selection is highlighted. Additionally, the research includes a simple mathematical model to analyze the available options. Finally, it presents conclusions and recommendations aimed at improving the technique selection process in the public sector.